Application of laser cladding welding wire in hydraulic support column
By using laser cladding welding wire containing FeTi30-A on the hydraulic support column, the process parameters are optimized, and the problem of insufficient hardness and corrosion resistance of the hydraulic support column cladding layer in the prior art is solved, and a high hardness and corrosion-resistant cladding layer preparation is achieved, reducing the cost and defect rate.
Patent Information
- Application Number
- CN202211691211.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-12-27
AI Technical Summary
In use, hydraulic support columns need to stably obtain a cladding layer with high hardness, corrosion resistance and defects. However, in the prior art, powder laser cladding has low utilization rate and high cost, and there are slag and splash problems in the silk laser cladding, resulting in high defect rate.
The laser cladding welding wire containing FeTi30-A is used to prepare a cladding layer on the surface of the hydraulic support column through wire laser cladding technology, and optimize the composition and process parameters of the flux core welding wire, including laser power, cladding speed and wire feeding speed, to form a high-hardness and corrosion-resistant cladding layer.
A cladding layer with high hardness (53-55HRC) and neutral salt spray corrosion resistance (over 300 hours) was achieved on the hydraulic support column, reducing defect rate and cost and improving process performance.
Smart Images

Figure CN115948738B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and in particular relates to an application of a laser cladding welding wire in a hydraulic support column. Background Art
[0002] At present, the commonly used surface treatment processes for hydraulic support cylinders are electroplating and laser cladding. In view of the geological conditions in the mine environment, the electroplating process has good adaptability, but it has large environmental pollution, and there are many disadvantages in the quality, performance, overhaul cycle, and maintenance costs of the coating. The laser cladding process is an advanced and environmentally friendly additive manufacturing technology that can better meet the long-life requirements of coal mine fully mechanized mining supports.
[0003] Laser cladding of hydraulic support columns often uses powder as consumables, which has low utilization rate, high cost and lack of competitiveness. However, wire laser cladding technology is applied to hydraulic support columns in coal mines. In order to obtain a wire cladding layer that meets service requirements, the cladding layer needs to have sufficient corrosion resistance to withstand the complex working environment of coal mining faces. In addition to corrosion, wear and failure of hydraulic support columns during use is also very common, so the wire cladding layer should also maintain a high hardness to resist wear.
[0004] When preparing the cladding layer, wire laser cladding is different from powder laser cladding. The influence of slag and spatter on cladding needs to be considered. Materials with high slag content and large spatter will form slag inclusions, which will directly affect the multiple overlaps and secondary cladding of the cladding layer, resulting in a high defect rate, which in turn affects the prepared cladding layer. Therefore, when performing wire laser cladding, whether the wire can stably obtain a high-hardness, corrosion-resistant, and low-defect cladding layer under the action of the laser heat source is the key to promoting the large-scale application of wire laser cladding technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide an application of a laser cladding welding wire in a hydraulic support column to solve the problem in the prior art that the hydraulic support column needs to stably obtain a high-hardness, corrosion-resistant, and low-defect cladding layer.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] Application of a laser cladding welding wire in a hydraulic support column, wherein the laser cladding welding wire contains FeTi30-A;
[0008] The laser cladding welding wire is used to prepare a cladding layer on the surface of a hydraulic support column through a wire laser cladding technology with a laser power of 3000W, a cladding speed of 22mm / s, and a wire feeding speed of 60mm / s; in terms of mass fraction, the cladding layer has the following components: C: 0.20-0.35%; Si: 0.30-0.50%; Mn: 0.60-1.20%; Cr: 18.80-20.60%; Ni: 1.40-2.40%; Mo: 0.20-0.80%; Al: 0.35-0.58%; Ti: 1.10-2.00%; B: 0.20%-0.70%, and the remainder is Fe; and the laser cladding layer contains TiC.
[0009] A further improvement of the present invention is:
[0010] Preferably, the preparation process of the laser cladding welding wire is: placing the mixed metal in a weld skin, flipping the weld skin so that the weld skin wraps the mixed metal powder; and pulling the weld skin wrapped with the mixed metal powder to a target diameter to obtain the welding wire.
[0011] Preferably, the flux core is a mixed metal powder; the composition of the flux core changes with the change of the welding skin material;
[0012] Preferably, when the weld skin is 430 stainless steel strip, the composition of the flux core is, by mass fraction, C: 0.70-1.20%; Si: 0.5-0.9%; B: 1.50-2.80%; Mn: 2.00-4.00%; Cr: 26.00-31.00%; Ni: 5.00-8.00%; Mo: 1.00-3.00%; FeTi30-A: 20-30%; and the balance is Fe.
[0013] Preferably, when the weld skin is 410 stainless steel strip, the composition of the flux core is, by mass fraction, C: 0.70-1.20%; Si: 0.36-0.76%; B: 1.50-2.80%; Mn: 2.00-4.00%; Cr: 36.50-41.50%; Ni: 4.80-7.70%; Mo: 1.00-3.00%; FeTi30-A: 20-30%; and the balance is Fe.
[0014] After the mixed metal powders are mixed, vacuum drying treatment is performed.
[0015] The powder filling rate in the flux-cored welding wire is 30wt.%-33wt.%.
[0016] The diameter of the flux-cored welding wire is 1.0-1.2 mm.
[0017] The hardness of the cladding layer is 53-55HRC, and the neutral salt spray corrosion resistance time is greater than 300 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention discloses an application of a laser cladding welding wire in a hydraulic support column. During the application process, FeTi30 is added to the welding wire, and the amount of FeTi30 added is related to carbon powder, so that C powder will generate a TiC reinforcement phase with FeTi30 in situ, avoiding excessive non-metallic oxidation to form spatter. By optimizing the content of added Si and B elements, Si and B are the main elements for slag formation, and under the premise of maintaining the fluidity of the molten pool, their content is reduced to reduce the amount of slag. The optimized flux-cored welding wire of the present invention has a powder mixture inside, and its composition is controllable, and the composition can be adjusted and controlled according to the needs of the cladding layer. At the same time, because of the powdery state, the powder can be quickly melted during the laser cladding process, and the molten pool formed during the laser cladding process has good fluidity, and the cladding layer formed has good uniformity of structure, and there is less spatter and smoke in the cladding process, and less slag is generated. The TiC reinforcement in the cladding layer finally generated by the welding wire of the present invention is generated by an in-situ autogenous technology. Compared with the traditional external addition method, the problems of particle burning, melting and decomposition of the reinforcement phase are avoided. The reinforcement in the prepared cladding layer is small in size, pollution-free on the surface, and has high interface bonding strength. At the same time, with the precipitation of part of TiC, the precipitation of excessive chromium carbide along the austenite grain boundary is avoided, thereby effectively preventing intergranular corrosion, thereby greatly improving the overall performance of the cladding layer.
[0020] Furthermore, the flux-cored welding wire is designed with martensite structure as the matrix structure of the laser cladding layer, and by adding Ti and Nb alloy elements to form an endogenous (Nb, Ti)C hard phase, the preparation of a high-hardness, wear-resistant and high-performance wire laser cladding layer is achieved, meeting the requirements for the continued service of the hydraulic support; the reinforcing phase selected by the present invention has good wettability with the matrix, thereby avoiding the problem of cracking caused by the reinforcing phase during the cladding process.
[0021] Furthermore, the cladding layer is essentially an Fe-based cladding layer, which is mainly formed by laser cladding on the surface of the hydraulic support column (the material is carbon steel). The main elements of both are Fe, so the thermal expansion coefficients of the two are similar, and the cladding layer finally formed has strong resistance to cracking and spalling.
[0022] Furthermore, the flux-cored welding wire is used for laser cladding to prepare corrosion-resistant and high-hardness laser cladding layers. The powder formula is easy to obtain, the wire production efficiency is high, the cost is low, and the application prospects are broad. The present invention adopts the flux-cored welding wire preparation technology, and the final composition of the flux-cored welding wire is achieved through steel strip and powder together. Compared with the traditional solid welding wire production that requires smelting steel, it has a short cycle, quick results, and low cost. The types of alloy elements of the flux-cored welding wire of the present invention can be quickly adjusted according to demand, and the welding wire drawing process is simple. The developed welding wire has a wire diameter of 1.0-1.2mm, and can also be used in MIG and TIG welding processes, with a wide range of applications.
[0023] Furthermore, the powder formula provided by the present invention is combined with 430 stainless steel strip or 410 stainless steel strip, and C and FeTi30 powder are added to be used as a deoxidizer and degassing agent during the laser cladding process to achieve in-situ reaction to generate TiC reinforcement phase, thereby achieving high hardness index, corrosion resistance and stability of the cladding layer. Combined with a certain Ni content, it is ensured that the high hardness cladding layer does not crack.
[0024] Furthermore, the cladding layer prepared by this method finally forms a cladding layer with high corrosion resistance and high hardness as a coating, and the coating is a martensitic stainless steel type material. The surface hardness of the functional coating prepared by wire laser cladding can reach 53-55HRC (average value ≥ 54HRC), and the material has excellent resistance to neutral environment corrosion. Under the conditions of "GBT10125 Artificial Atmosphere Corrosion Test Salt Spray Test", when the neutral salt spray corrosion test is tested, the corrosion rating of the surface of the material after 300 hours of corrosion is in accordance with "GBT6461 Rating of samples and specimens of metal and other inorganic coatings on metal substrates after corrosion tests", which can reach the highest level of 9 or above, and is not prone to corrosion. It has important engineering practical value for reducing the repair cost of hydraulic support cylinders and promoting the application of green laser surface modification technology in the coal mining industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The microstructure of the cladding layer of the flux-cored welding wire prepared in Example 2 of the present invention after laser cladding. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0027] One embodiment of the present invention discloses an application of a laser cladding welding wire in a hydraulic support column, and the application process includes two steps:
[0028] Step 1, prepare a flux-cored welding wire; the flux-cored welding wire is a high-hardness, low-slag, low-splash, endogenous ceramic-reinforced phase laser-clad flux-cored welding wire, comprising a flux core and a welding skin, the flux core is arranged in the welding skin, the flux core is wrapped by the welding skin, and the welding skin is a stainless steel strip.
[0029] The stainless steel strip can be adjusted according to the actual situation, such as using 430 stainless steel strip or 410 stainless steel strip. In order to generate the target cladding layer content, the flux core component is adjusted accordingly with the adjustment of the stainless steel strip type. The flux core wire powder filling rate is 30wt.%-33wt.%.
[0030] Specifically, when the weld skin is a 430 stainless steel strip, the powder is composed of a mixed metal powder, and the mixed metal powder is composed of the following raw material components by mass percentage: C: 0.70-1.20%; Si: 0.50-0.90%; B: 1.50-2.80%; Mn: 2.00-4.00%; Cr: 26.00-31.00%; Ni: 5.00-8.00%; Mo: 1.00-3.00%; FeTi30-A: 20-30%; and the balance is Fe.
[0031] Specifically, when the weld skin is a 410 stainless steel strip, the powder is composed of a mixed metal powder, and the mixed metal powder is composed of the following raw material components by mass percentage: C: 0.70-1.20%; Si: 0.36-0.76%; B: 1.50-2.80%; Mn: 2.00-4.00%; Cr: 36.50-41.50%; Ni: 4.80-7.70%; Mo: 1.00-3.00%; FeTi30-A: 20-30%; and the balance is Fe.
[0032] Specifically, when preparing the flux core, each metal powder is weighed according to the target flux core composition, the weighed metal powders are mixed by a mixer or other mixing methods, and then dried in a vacuum furnace to obtain mixed and dried metal powders, the dried metal powders are placed in an expanded weld skin, the metal powders are wrapped with the weld skin, and then drawn to form a welding wire, the diameter of the welding wire is φ1.0-1.2mm.
[0033] Step 2, through laser cladding, after melting the welding wire on the surface of the hydraulic support, a laser cladding layer is formed on the surface of the hydraulic support. The parameters of the laser cladding process are laser power 3000w, cladding speed 22mm / s, and wire feeding speed 60mm / s. The cladding layer is a coating with corrosion resistance and high hardness. The prepared coating belongs to the martensitic stainless steel type material. By adding alloy elements to improve strength and toughness and optimizing slag-forming elements such as Si and B, the wire material has better process performance in the cladding process, less smoke, less slag, and less spatter. The cladding layer has good corrosion resistance and high hardness and plastic toughness. By adopting the preparation technology of flux-cored welding wire, it can be prepared into metal wire by drawing.
[0034] Specifically, in terms of mass fraction, the composition of the cladding layer is C: 0.20-0.35%; Si: 0.30-0.50%; Mn: 0.60-1.20%; Cr: 18.80-20.60%; Ni: 1.40-2.40%; Mo: 0.20-0.80%; Al: 0.35-0.58%; Ti: 1.10-2.00%; B: 0.30%-0.70%.
[0035] The present invention ensures that the cladding layer has high hardness and corrosion resistance through reasonable allocation of elements, and the process performance is less slag and less splashing to reduce the occurrence of slag inclusion defects in the cladding process. The functions of the main alloy elements in the metal wire material formula composition of the present invention are as follows:
[0036] Chromium (Cr): Cr can improve the strength of α-Fe based on solid solution strengthening. Here, the role of adding Cr is mainly to ensure that the cladding layer can resist neutral salt spray corrosion (NSS) for more than 300 hours by virtue of its excellent corrosion resistance. In the present invention, 26.00-30.00% of Cr elements are added to the powder with a 430 stainless steel strip and a filling rate of 30-33wt.%. In the powder with a 410 stainless steel strip and a filling rate of 30-33wt.%, 36.50-41.50% of Cr elements are added.
[0037] Molybdenum (Mo): Like Cr, Mo has the effects of solid solution strengthening and improving corrosion resistance. However, the solid solution strengthening effect of Mo is stronger than that of Cr, and the effect on corrosion resistance is lower than that of Cr. In the present invention, the strength of the cladding layer is mainly guaranteed by the endogenous hard phase. Therefore, in order to avoid cracking of the cladding layer, Mo, an element that can significantly improve the strength of the cladding layer, is reduced. In addition, the reduction of Mo can also reduce the production cost of the material. In the present invention, 1.00-3.00% of the Mo element is added to the powder in combination with 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-33wt.%.
[0038] FeTi30: FeTi30 belongs to titanium iron, which is used as a deoxidizer and degasser during the cladding process. The deoxidizing ability of titanium in FeTi30 is much higher than that of silicon and manganese, and it can reduce the segregation of the cladding layer and improve the strength, corrosion resistance and stability of the cladding layer. At the same time, the titanium in FeTi30 reacts with C to generate TiC brittle phase in situ. TiC brittle phase has high hardness. If the amount of FeTi30 added is large, a large amount of TiC phase will be generated, and the cladding layer is prone to cracking. In addition, the generation of TiC should be coordinated with the content of added C powder. Therefore, after comprehensive consideration, the present invention is combined with 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-33wt.%, and 20.0-30.0% of FeTi30 powder is added to the powder.
[0039] Nickel (Ni): Ni also plays a role in corrosion resistance and solid solution strengthening. The main purpose of adding Ni in the present invention is to improve its plastic toughness and avoid cracking of the cladding layer. In the present invention, 5.00-8.00% Ni is added to the powder with 430 stainless steel strip and a filling rate of 30-33wt.%. 4.80-7.70% Ni is added to the powder with 410 stainless steel strip and a filling rate of 30-33wt.%.
[0040] Silicon (Si) and manganese (Mn): The role of Si and Mn in the present invention is mainly to combine deoxidation, reduce the oxygen content in the cladding layer, and prevent the generation of pores. Mn also has a certain effect on improving the strength of the cladding layer. In the present invention, 430 stainless steel strip and a filling rate of 30-33wt.% are combined, and 1.00-1.50% of Si element and 2.00-4.00% of Mn element are added to the powder. In the present invention, 410 stainless steel strip and a filling rate of 30-33wt.% are combined, and 0.36-0.76% of Si element and 2.00-4.00% of Mn element are added to the powder.
[0041] Carbon (C): C is an essential element for forming martensite. In the present invention, the C element is mainly provided by 430 stainless steel strip and added C powder, which will react with FeTi 30 In-situ generation of TiC reinforcement phase. In the present invention, 430 stainless steel strip or 410 stainless steel strip and a filling rate of 30-33wt.% are combined, and 0.70-1.20% of C element is added to the powder.
[0042] Preferably, the metal flux-cored welding wire is a martensitic stainless steel wire material with a diameter of φ1.0 mm-φ1.2 mm.
[0043] The invention discloses a use of a high-hardness, low-slag, low-splash endogenous ceramic-reinforced phase laser-cladding flux-cored welding wire, wherein the laser-cladding wire is used for laser-cladding treatment of the surface of a hydraulic support column.
[0044] Furthermore, according to the present invention, the use of a high-hardness, low-slag, low-splash endogenous ceramic reinforced phase laser cladding flux-cored welding wire is used for laser cladding treatment of the surface of relevant parts in the hydraulic support. The hardness of the surface laser cladding coating reaches 53-55HRC (average value ≥54HRC), and the neutral salt spray corrosion (NSS) resistance of the surface laser cladding coating reaches more than 300 hours.
[0045] The following is further described in conjunction with specific embodiments:
[0046] Example 1
[0047] Step 1, weighing metal powders according to the following composition by mass fraction: C, 0.7%; Si, 0.73%; Mn, 4.0%; Cr, 26%; Ni, 5.0%; Mo, 30%; FeTi30, 20%; B, 1.5%; the balance is iron, placing the weighed mixed metal powders in a 430 stainless steel strip, wrapping the mixed metal powders with the 430 stainless steel strip, with the filling rate of the powder being 30wt.%, and drawing to prepare a flux-cored welding wire.
[0048] Step 2, the flux-cored welding wire prepared in step 1 is laser clad on the surface of the hydraulic support column to prepare a multi-layer cladding layer (not less than 5 layers), and the Rockwell hardness (HRC) of different parts of the material is measured to be 53.2, 54.9, 55.2, 55.4 and 54.3, respectively, with an average value of 54.56; the composition of the prepared cladding layer is: C, 0.21%; Si, 0.43%; Mn, 1.2%; Cr, 18.8%; Ni, 1.4%; Mo, 0.8%; B, 0.31%; Ti, 1.1%, Al, 0.35%, and the balance is Fe. According to the "Test Method for Welding Anti-spatter Agent", the spatter residual rate of the cladding process is 0.84%.
[0049] Embodiment 2:
[0050] Step 1, weigh metal powders according to the following composition by mass fraction: C, 1.2%; Si, 0.9%; Mn, 3.0%; Cr, 31%; Ni, 8.0%; Mo, 2%; FeTi30, 30%; B, 2.8%; the remainder is iron, put the weighed mixed metal powders into a 430 stainless steel strip, wrap the mixed metal powders with the 430 stainless steel strip, the filling rate of the powder is 33wt.%, and draw to prepare a flux-cored welding wire.
[0051] Step 2, the flux-cored welding wire prepared in step 1 is laser clad on the surface of the hydraulic support column to prepare a multi-layer cladding layer (not less than 5 layers), and the Rockwell hardness (HRC) of different parts of the material is measured to be 55.2, 54.9, 54.8, 55.0 and 53.7, respectively, with an average value of 54.7; the composition of the prepared cladding layer is: C, 0.35%; Si, 0.5%; Mn, 0.84%; Cr, 20.57%; Ni, 2.38%; Mo, 0.52%; B, 0.7; Ti, 2.0%, Al, 0.58%, and the balance is Fe. According to the "Test Method for Welding Anti-spatter Agent", the spatter residual rate of the cladding process is 0.89%.
[0052] The laser cladding layer prepared in Example 2 has a structure as follows Figure 1 As shown: the cladding layer is mainly composed of martensite structure, with fine and uniform grains, uniform distribution of carbides, and no defects such as cracks and pores.
[0053] Embodiment 3:
[0054] Step 1, weighing metal powders according to the following composition by mass fraction: C, 1.0%; Si, 0.5%; Mn, 2.0%; Cr, 28.5%; Ni, 7.0%; Mo, 1%; FeTi30, 25%; B, 2.1%; the remainder is iron, placing the weighed mixed metal powders in a 430 stainless steel strip, wrapping the mixed metal powders with the 430 stainless steel strip, the filling rate of the powder is 31wt.%, and drawing to prepare a flux-cored welding wire.
[0055] Step 2, the flux-cored welding wire prepared in step 1 is laser clad on the surface of the hydraulic support column to prepare a multi-layer cladding layer (not less than 5 layers). The Rockwell hardness (HRC) of different parts of the material is measured to be 53.4, 57.1, 56.9, 55.1 and 55.1, respectively, with an average value of 55.5; the composition of the prepared cladding layer is: C, 0.28%; Si, 0.3%; Mn, 0.6%; Cr, 19.3%; Ni, 2.4%; Mo, 0.2%; B, 0.52; Ti, 1.8%, Al, 0.46%, and the remainder is Fe. According to the "Test Method for Welding Anti-spatter Agent", the spatter residual rate of the cladding process is 0.78%.
[0056] Embodiment 4:
[0057] Step 1, weigh metal powders according to the following composition by mass fraction: C, 0.7%; Si, 0.36%; Mn, 2.0%; Cr, 38.4%; Ni, 4.8%; Mo, 1%; FeTi30, 20%; B, 2.8%; the remainder is iron, put the weighed mixed metal powders into a 430 stainless steel strip, wrap the mixed metal powders with the 430 stainless steel strip, the filling rate of the powder is 30wt.%, and draw to prepare a flux-cored welding wire.
[0058] Step 2, the flux-cored welding wire prepared in step 1 is laser clad on the surface of the hydraulic support column to prepare a multi-layer cladding layer (not less than 5 layers), and the Rockwell hardness (HRC) of different parts of the material is measured to be 52.8, 56.4, 55.3, 55.7 and 54.5, respectively, with an average value of 54.95; the composition of the prepared cladding layer is: C, 0.2%; Si, 0.30%; Mn, 0.6%; Cr, 19.5%; Ni, 1.43%; Mo, 0.24%; B, 0.7%, Ti, 1.1%, Al, 0.35%, and the balance is Fe. According to the "Test Method for Welding Anti-spatter Agent", the spatter residual rate of the cladding process is 0.91%.
[0059] Embodiment 5:
[0060] Step 1, weighing metal powders according to the following composition by mass fraction: C, 1.2%; Si, 0.58%; Mn, 4.0%; Cr, 36.5%; Ni, 7.7%; Mo, 3%; FeTi30, 20%; B, 2.1%; the remainder is iron, placing the weighed mixed metal powders in a 430 stainless steel strip, wrapping the mixed metal powders with the 430 stainless steel strip, the filling rate of the powder is 33wt.%, and drawing to prepare a flux-cored welding wire.
[0061] Step 2, the flux-cored welding wire prepared in step 1 is laser clad on the surface of the hydraulic support column to prepare a multi-layer cladding layer (not less than 5 layers), and the Rockwell hardness (HRC) of different parts of the material is measured to be 54.9, 55.7, 55.1, 56.3 and 54.5, respectively, with an average value of 55.3; the composition of the prepared cladding layer is: C, 0.35%; Si, 0.43%; Mn, 1.2%; Cr, 18.9%; Ni, 2.4%; Mo, 0.78%; B, 0.48%; Ti, 2.0%, Al, 0.58%, and the remainder is Fe. According to the "Test Method for Welding Anti-spatter Agent", the spatter residual rate of the cladding process is 0.83%.
[0062] Embodiment 6:
[0063] Step 1, weighing metal powders according to the following composition by mass fraction: C, 0.86%; Si, 0.76%; Mn, 3.2%; Cr, 41.5%; Ni, 5.8%; Mo, 2.1%; FeTi30, 26%; B, 1.5%; the remainder is iron, placing the weighed mixed metal powders in a 430 stainless steel strip, wrapping the mixed metal powders with the 430 stainless steel strip, the filling rate of the powder is 31wt.%, and drawing to prepare a flux-cored welding wire.
[0064] Step 2, the flux-cored welding wire prepared in step 1 is laser clad on the surface of the hydraulic support column to prepare a multi-layer cladding layer (not less than 5 layers), and the Rockwell hardness (HRC) of different parts of the material is measured to be 54.8, 53.3, 54.1, 55.3 and 54.5, respectively, with an average value of 54.6; the composition of the prepared cladding layer is: C, 0.29%; Si, 0.5%; Mn, 0.93%; Cr, 20.6%; Ni, 1.92%; Mo, 0.56%; B, 0.30%; Ti, 1.86%, Al, 0.48%, and the remainder is Fe. According to the "Test Method for Welding Anti-spatter Agent", the spatter residual rate of the cladding process is 0.86%.
[0065] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. Application of laser cladding welding wire in hydraulic support column, characterized in that: The laser cladding welding wire is used to prepare a cladding layer on the surface of the hydraulic support column by using a wire laser cladding technology with a laser power of 3000W, a cladding speed of 22mm / s, and a wire feeding speed of 60mm / s; the cladding layer has the following components by mass fraction: C: 0.20-0.35%; Si: 0.30-0.50%; Mn: 0.60-1.20%; Cr: 18.80-20.60%; Ni: 1.40-2.40%; Mo: 0.20-0.80%; Al: 0.35-0.58%; Ti: 1.10-2.00%; B: 0.20%-0.70%, and the balance is Fe; the cladding layer contains TiC; The welding wire comprises a flux core and a welding skin, wherein the flux core is a mixed metal powder; the composition of the flux core changes with the change of the welding skin material, and the welding skin is a 430 stainless steel strip or a 410 stainless steel strip; When the weld skin is 430 stainless steel strip, the composition of the flux core is calculated by mass fraction: C: 0.70-1.20%; Si: 0.5-0.9%; B: 1.50-2.80%; Mn: 2.00-4.00%; Cr: 26.00-31.00%; Ni: 5.00-8.00%; Mo: 1.00-3.00%; FeTi30-A: 20-30%; the balance is Fe; When the weld skin is 410 stainless steel strip, the composition of the flux core is calculated by mass fraction: C: 0.70-1.20%; Si: 0.36-0.76%; B: 1.50-2.80%; Mn: 2.00-4.00%; Cr: 36.50-41.50%; Ni: 4.80-7.70%; Mo: 1.00-3.00%; FeTi30-A: 20-30%; the balance is Fe; The filling rate of the powder in the welding wire is 30wt.%-33wt.%; The diameter of the welding wire is 1.0-1.2 mm; The hardness of the cladding layer is 53-55HRC, and the neutral salt spray corrosion resistance time is greater than 300 hours.
2. The application of a laser cladding welding wire in a hydraulic support column according to claim 1 is characterized in that: The preparation process of the laser cladding welding wire is as follows: placing the mixed metal in a welding skin, turning the welding skin over so that the welding skin wraps the mixed metal powder; and pulling the welding skin wrapped with the mixed metal powder to a target diameter to obtain the welding wire.
3. The application of a laser cladding welding wire in a hydraulic support column according to claim 1 is characterized in that: After the mixed metal powders are mixed, vacuum drying treatment is performed.
Citation Information
Patent Citations
Method for machining hydraulic support column through outwards-feeding plasma fusing and preparation method of flux-cored wire applied to same
CN104475949A
Reinforced abrasion-resistant surface welding flux-cored wire made of in-situ generated titanium carbide and method for manufacturing reinforced abrasion-resistant surface welding flux-cored wire
CN104625487A
Wear-resistant and corrosion-resistant flux-cored wire for TIG-P surfacing of hydraulic bracket member
CN112122821A
Metal wire material for laser cladding and preparation method and application thereof
CN114525447A